Guide to energy management - Capehart, B. L. (Barney L.) (Fairmont Press ; Distributed by CRC/Taylor & Francis, 2006)
"Now in its fifth edition, this text is the manager's guide to the most important areas of energy cost cutting. Written and revised by three of the most respected energy professionals in the industry, this book examines the fundamental objectives of energy management and illustrates techniques and tools proven effective for achieving results. Subjects such as lighting, combustion processes, industrial wastes, and steam generation and distribution are thoroughly explored and updated with the latest information. Additional topics include distributed generation, energy auditing, rate structures, economic evaluation, HVAC optimization, control systems, process energy management, and renewable energy." -- Publisher.